Does climate-smart agriculture improve household income and food security? Evidence from Southern Ethiopia - Abrham Belay; Alisher Mirzabaev; John W. Recha; Christopher Oludhe; Philip M. Osano; Zerihun Berhane; Lydia A. Olaka; Yitagesu T. Tegegne; Teferi Demissie; Chrispinus Mutsami; Dawit Solomon (Environment, Development and Sustainability, 2023)
Climate change threatens African countries' economic development and affects agriculture and food security. Ethiopia is especially vulnerable to the negative effects of climate change because its economy is dependent on climate-sensitive livelihoods that have limited potential for adaptation. Emerging evidence indicates that climate-smart agriculture (CSA) can help smallholder farmers adapt to climate change and increase agricultural productivity, thereby enhancing household income and food security. In the study area, different CSA practices have been adopted to mitigate the negative effects of climate change and improve agricultural productivity, income, and food security. Therefore, this study examines the impact of CSA practices on household income and food security in southern Ethiopia. A total of 385 households were selected using multistage sampling. Primary and secondary data were used, and propensity score matching with different types of matching algorithms, such as nearest neighbor, kernel, and radius matching, was employed to quantify the conditional impacts of CSA intervention on farm income and food security. In comparison with non adopters~farmers that have adopted CSA practices had a higher~food consumption score between 6.27 and 8.15, which was statistically significant at the 1% level. Overall, 34.55% of interviewed households had acceptable food consumption scores, 44.68% had borderline, and 20.77% had poor~food consumption scores. Furthermore, households that adopted CSA practices had a 20.30% higher average annual farm income per hectare~than non-adopters. The study suggests that effective extension services, accurate climate information, and sound~policy support are required to promote and scale up CSA measures in the study area to improve farmers' adaptive capacity, farm income, and food security.
Keywords: 330; Climate change adaptation; Climate-smart agriculture practices; Food security; Farm income; Propensity score matching approach; Southern Ethiopia